Antioxidant Effect in Nasopharyngeal Cancer Histopathology Degree on 40 PPM Formaldehyde-Inducted Rattus novergicus - Wibawa, Putu Arta; Wedayani, Anak Agung Ayu Niti; Prihatina, Lale Maulin; Yuliani, Eka Ari; Pratiwi, Sekar (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Formaldehyde exposure, implicated on the development of nasopharyngeal cancer (NPC), remains a significant concern worldwide, with increasing incidence, morbidity, and mortality cases. This study eager to investigate the antioxidant effect on degree of histopathology from formaldehyde exposure, assessing nasopharyngeal dysplasia progression toward malignancy. Rattus norvegicus divided equally into four groups: control, placebo, formaldehyde-induced (40 PPM), and formaldehyde-induced with antioxidant, followed by dysplasia degree examination under light microscope. The result revealed severe dysplasia in the formaldehyde group, indicating non-keratinizing squamous cell carcinoma. Additionally, antioxidant-treated group presented reduced severity, with lower degree of dysplasia. This result is indicating positive improvement of antioxidant effect toward NPC malignancy, supporting previous studies and further confirming genotoxicity and irritability of formaldehyde. Nevertheless, limitations, existed with lack of sample studied and dose-response analysis, were demanding deeper study need to be done.